(untitled) - Sprague, Jo (Fort Worth, 2000)
The book is a compendium of principles, examples, and exercise that covers the issues one commonly confronts in preparing and delivering a speech.
Keywords: English language,English language,Public speaking,Speech; Rhetoric,Handbooks, manuals, etc,Technical english,Handbooks, manuals, etc,Study and teaching